2022
DOI: 10.1128/jvi.01974-21
|View full text |Cite
|
Sign up to set email alerts
|

Host T Cell Dedifferentiation Effects Drive HIV-1 Latency Stability

Abstract: The development of therapies to eliminate the latent HIV-1 reservoir is hampered by our incomplete understanding of the biomolecular mechanism governing HIV-1 latency. To further complicate matters, recent single cell RNA-seq studies reported extensive heterogeneity between latently HIV-1-infected primary T cells, implying that latent HIV-1 infection can persist in greatly differing host cell environments. We here show that transcriptomic heterogeneity is also found between latently infected T cell lines, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 235 publications
0
1
0
Order By: Relevance
“…A recent singlecell RNA sequencing study reported that latently HIV-1-infected T cells exhibited a dedifferentiated phenotype, characterized by the loss of T cell-specific markers and gene regulation profiles reminiscent of hematopoietic stem cells. As reported for stem cells, latently HIV-1-infected T cells efficiently forced lentiviral superinfections into a latent state and favored glycolysis [67]. These results highlight the pivotal role of host cell development and metabolism in defending against pathogen infections.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 73%
“…A recent singlecell RNA sequencing study reported that latently HIV-1-infected T cells exhibited a dedifferentiated phenotype, characterized by the loss of T cell-specific markers and gene regulation profiles reminiscent of hematopoietic stem cells. As reported for stem cells, latently HIV-1-infected T cells efficiently forced lentiviral superinfections into a latent state and favored glycolysis [67]. These results highlight the pivotal role of host cell development and metabolism in defending against pathogen infections.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 73%
“…[59] On the contrary, the latest study showed that, compared with uninfected T cells (Jurkat), three latently HIV-1-infected T cells (CA5, EF7, and CG3) produced significantly more lactate, confirming the metabolic preference for glycolysis. [71] Therefore, the specific relationship between HIV-1 latency and glucose metabolism is worthy of exploration in the future.…”
Section: Potential Application Of Metabolic Features Of Hiv-1 Infectionmentioning
confidence: 99%